The role of positive and negative reinforcement by coaches in the acquisition of new motor skills depending on the present sport motive - Schröder, S. (Scientific Journal of Sport and Performance, 2025)
The results of this pilot study should allow conclusions to be drawn about the influence of the trainer's approach and the motor learning behaviour depending on the existing motive structure. To this end, two groups were randomly formed, each of which watched a learning video in which six steps for learning to juggle were shown. The two groups were randomly given either a positively or negatively reinforced speech in sound and text. The 27 participants (8 girls, 19 boys, mean age: 17.74, SD = 0.86) are sports students supported by the Olympic training centre. The results showed a dependence of motor learning performance on trainer response (meanpos = 4.93, meanneg = 4.27, p = .030 (one-sided), d = -0.74). In the present study, the mean differences between the hope- and fear-motivated groups show large differences in this respect, but these are not significant, certainly due to the small sample size (meanfear = 4.2, meanhope = 5.0, p = .103). It was interesting to note that the fear-motivated athletes in particular benefited from receiving positive coaching instructions. The calculation of the effect size confirms this assumption (d = .366). The covariance analysis also indicate that the motor learning performance depends on the positive or negative trainer instruction when these are adjusted for the respective co-variables skin conductivity, blood volume pulse and present motive structure (partial n² = 0.128-0.139). The results show that the positive influence of the coach's approach in the context of motor learning is of great importance.